New curious genus of the subfamily Cladonotinae (Orthoptera: Tetrigidae) from Borneo Island with remarks on the classification of this subfamily - Storozhenko, Sergey Yu. (Zootaxa, 2023)
A new monotypic genus Trusmaditetrix gen. nov. (type species: Trusmaditetrix complanata sp. nov.) is described from Malaysia. New tribe Trusmaditetrigini trib. nov. is established for six genera of Cladonotinae (Trusmaditetrix gen. nov., Devriesetettix Tumbrinck, Eurymorphopus Hancock, Ichikawatettix Tumbrinck, Planotettix Tumbrinck, and Tepperotettix Rehn). A key to genera and an annotated list of the genera and species of the new tribe are also provided. The species Eurymorphopus dubius Günther, 1974 from Mauritius is placed in the genus Morphopoides Rehn, 1930 and a new combination is proposed: M. dubius (Günther, 1974), comb. nov.